Delay tactic in arbitration proceedings [electronic resource] - Mohd. Khairul Anuar Jalil, 1985- author; Jamaludin Yaakob, supervisor; Fakulti Alam Bina (2015)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan) - Universiti Teknologi Malaysia, 2015